Designing a Web-Based Zakat Calculator Using Streamlit: A Case Study of BAZNAS Banyumas Regency - Rojulan Fayadul Mujahid; Muhammad Romadhona Kusuma (Yayasan Mitra Peduli Indonesia, 2025)
Zakat is an important instrument for distributing welfare among Muslims and requires accurate and transparent calculations. However, some people still have difficulty calculating zakat on their income independently. This study aims to design and implement a web-based Zakat Calculator application using the Streamlit framework, with a case study at the National Zakat Agency (BAZNAS) in Banyumas Regency. This application features an interactive interface, automatic calculations based on the current gold nishab, and flexible additional income features. The research method uses a Design Science Research (DSR) approach, with the following stages: problem identification, artifact design, implementation, and evaluation. The implementation results show that the application can facilitate muzaki (payers of zakat) in calculating zakat obligations quickly and accurately, and provides user-friendly information on the status of their obligations. This application also supports transparency in zakat collection at the regional level.